Find the best solutions to your questions at Westonci.ca, the premier Q&A platform with a community of knowledgeable experts. Get expert answers to your questions quickly and accurately from our dedicated community of professionals. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
[tex]\text{Given that,}~ f(x) =2x^2 -3x +1~ \text{and}~ g(x) = x+1[/tex]
[tex]f(g(x))\\\\=f(x+1)\\\\=2(x+1)^2 -3(x+1) +1\\\\=2(x^2 +2x +1) -3x -3 +1\\\\=2x^2 +4x +2-3x -2\\\\=2x^2 +x\\\\=x(2x+1)[/tex]
Answer:
f(g(x)) = 2x² + x
Step-by-step explanation:
f(x) = 2x² – 3x + 1 and g(x) = x + 1
→substitute g(x) for x + 1
f(g(x)) = f (x + 1)
→substitute x for x+1 into the f(x) equation
f(g(x)) = f (x + 1) = 2(x+1)² – 3(x+1) + 1
→calculate
f(g(x)) = 2(x+1)² – 3(x+1) + 1 , square x+1
f(g(x)) = 2( x²+2x+1) -3(x+1) +1 , distribute in parenthesis
f(g(x)) = 2x²+4x+2 -3x -3 +1, combine like terms
f(g(x)) = 2x² + x
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.